Working multisectorally to improve nutrition: Global lessons and current status in India - Garrett, James L.; Kadiyala, Suneetha; Kohli, Neha (International Food Policy Research Institute, 2014)
To identify global lessons in working multisectorally for nutrition and to ascertain what lessons could be applied to the Indian context, a team from POSHAN examined global best practices from other countries, including Bolivia, Colombia, Peru, Senegal, and Thailand (Cunningham 2011; Garrett & Natalicchio 2011; Meija-Acosta 2011; Hoey & Pelletier 2011; Heaver & Kachondam 2002). The team also performed a desk review of nutrition policies and programs in India at the national and select state levels that were designed to involve multiple sectors, ministries, or actors. The remainder of this note presents lessons learned from the global experiences, describes current multisectoral initiatives in India in nutrition, and makes recom-mendations that can ensure better implementation and sustainability of multisectoral approaches for nutrition in India.